Interculturality: experiences and challenges in/of University (Práxis Educativa, 2022)
Internationalization is a theme that has come to occupy the agenda in the last 20 years both of researchers, international organizations, governments and management of institutions. Thus, the objective proposed in this paper was to analyze the categories of thinking and operating interculturality, from the constitutive sociogenesis of the project of the Universidade Federal de Integração Latino-Americana (UNILA) and from the experiences of faculty and staff of this University, as well as understanding the internationalization of Higher Education in the context of the Western modernity/coloniality. The decolonial perspective brought epistemic bases necessary for the construction of the research. It is a qualitative research, based on exploratory research and documentary analysis. The main results demonstrate that interculturality is part of the University’s mission, built from a different project, from the majority of Brazilian universities. In addition, inclusion is part of its constitutive project and seeks to develop actions and initiatives aimed at interculturality, leveraging non-hegemonic knowledge.Keywords: UNILA. Internationalization. Decoloniality.